Programas para o desenvolvimento da ovinocaprinocultura na região dos inhamuns – ce, entre os anos de 2013 e 2014. - Araújo, Valéria de Jesus (Universidade Federal do Tocantins, 2023)
The Supervised aims to interaction between the knowledge acquired in the classroom and experience the reality of sheep and goat farming in the Brazilian Northeast . This was held between October 28, 2013 and January 31, 2014 , making workload of 360 hours . During this period it was possible to observe the activities and actions that are being performed and developed in the city of Taua, state of Ceará . As these actions are helping the local economy , and how they are changing the posture of the producers . Bringing growth and modernization of the chain . The sheep and goat farming have been on the rise in Brazil . It is a prominent activity in the socio - economic context of the whole country , especially the Northeast , which owns over 94 % of sheep and goats in the country . But it is still a very rough activity that has a significant lack of organization , which hinders the generation and dissemination of technologies in the properties . The producers did not even see their source of income and employment , as a business .